Parental bonding as a predictor of hope in adolescents - Izzaty, Rita Eka; Ayriza, Yulia (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
Hope plays an important role in individuals’ attempts to overcome various problems in a positive way and with positive results. This study aims to examine the effect of parent-child attachment on the existence of hope. The research method involved a quantitative approach. The accidental sampling technique was used to determine the sample and identified 400 adolescents consisting of junior and senior high school students aged 12-19 in Yogyakarta, Indonesia. Parent-child attachment was measured using the Parental Bonding Instrument, while expectation was measured using Snyder's Hope Scale. The data were analyzed using linear regression to predict the relationship between parent and child attachment and expectations. The results show that warm and loving care from the father (B = 0.37, p < .001] and the mother (B = 0.47, p < .001], as well as the provision of autonomy by the father (B = 0.52, p < .001] and mother (B = 0.38, p <.01] proved to be predictors of adolescent expectations, while over-protection from the father (B = 0.03, p> .05]) and the mother (B = -0.18, p> .05) were not predictors of the existence of hope. The implications of the research results could serve as a reference for the parenting practice and guidance to adolescents both in the contexts of family and school education.